PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN DAN KREATIVITAS TERHADAP HASIL BELAJAR MATA KULIAH MAKANAN NUSANTARA MAHASISWA PROGRAM STUDI TATA BOGA UNIVERSITAS NEGERI MEDAN - Nuwairy Hilda (JURNAL KELUARGA SEHAT SEJAHTERA, 2013)
ABSTRACT   This Study is aimed at finding out the learning achievement of students who were  taught by using picture media   and OHT media of learning Makanan Nusantara, a student with high creativity will achieve a higher learning  achievement compare to student with low creativity, Interaction between the use of media and creativity  influence the outcomes of learning makanan nusantara at Tata Boga Unimed. The population for this study were all the student’s on semester III of Tata Boga of Engineering Faculty of Medan State University, and 2 classes were taken as sample using purposive sampling. The quasi experiment method was used for this study by 2x2 factorial design, the data analysis was measured by two-way analize of Variance. To measure creativity level figural and verbal test is used, and two measure the achievement on Makanan Nusantara formative test using a multiple choice that consist of 55 items is used. The hypotheses result showed that the student learning outcomes  taught by picture media   is higher than a student who taught by OHT media on Makanan Nusantara,  student with high creativity will a chieve a higher learning outcomes compare to student with low creativity, There was interection between the use of media and the creativity in influencing the outcomes of learning makanan nusantara. Another finding shows that in the learning Makanan Nusantara the use of OHT learning media is   better for student whih high creativity and learning by picture  media   is better for student with low creativity. Kata Kunci : Media pembelajaran, kreatifitas, hasil belajar.